Popper's Nightmare - Parravicini, Jacopo (Organisms. Journal of Biological Sciences, 2022)
Epistemological relativism and authoritarianism are compressing political and intellectual freedoms by replacing facts with interpretations, as Karl Popper predicted several decades ago. Some suggestions to cope with this situation in science are provided.